CYBERBULLYING IN SCHOOLS: PREVENTION AND INTERVENTION STRATEGIES IN THE DIGITAL AGE - Cynthia Petra Haumahu; Criezta Korlefura; Yulian Hermanus Wenno (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Cyberbullying is one of the main challenges in schools in the digital age, where technological advances and the widespread use of social media have expanded the space for bullying among students. This phenomenon has a significant impact on students' mental health, academic achievement, and social well-being, with victims often experiencing psychological distress, anxiety, and even depression. This study uses a literature review method to identify forms of cyberbullying, its causes, and analyse effective prevention and intervention strategies in schools. The findings indicate that prevention efforts can be implemented through digital literacy education, character building, parental involvement, and the creation of a safe and inclusive school culture. Meanwhile, effective interventions involve psychological support, counselling services, and collaboration between schools, families, and digital platforms. With integrated and collaborative strategies, it is hoped that cases of cyberbullying in schools can be minimised, thereby creating a healthy learning environment that supports the optimal development of students in the digital era.